Effect of annealing temperature on microstructure and properties of the microtubes for GH4169 alloy - He Kehang; Zixin Yang; Shengli Guo; Baohong Zhu; Haochen Qiu; Shuaishuai Wu; Xuehui Yan; Wei Jiang (Materials Research Express, 2024)
The effects of annealing temperature on the recrystallization and grain boundary distribution characteristic for the drawn microtube of GH4169 alloy were studied by scanning electron microscope (SEM) equipped with an electron backscatter diffraction (EBSD) analysis system and transmission electron microscopy (TEM). The results demonstrated that at an annealing temperature of 850 °C, only a small proportion of recrystallization for the microtube underwent. As the annealing temperature increased, the proportion of recrystallization also increased. Specifically, at 900 °C, the proportion reached 95.8%, indicating complete recrystallization. Fine recrystallization grains were obtained with an average grain size of 4.73 μ m. As the annealing temperature is above 900 °C, the microtube also undergo complete recrystallization, and the grains grow up gradually. At 1000 °C, the average grain size grows to 7.42 μ m. The results also revealed that with the annealing temperature increasing, the proportion of Σ 3 grain boundary of the microtube was rising. The proportion of Σ 3 grain boundary increased from 30.1% to 34.2% with the annealing temperature increased from 900 °C to 1000 °C. Moreover, as the annealing temperature increased from 850 °C to 1000 °C, the room temperature tensile strength of the tube decreased from 1323 MPa to 965 MPa, the yield strength decreased from 1054 MPa to 523 MPa, and the fracture elongation increased from 10.2% to 31.2%.